COVID19 and otology/neurotology (2020)
The severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), responsible for the worldwide COVID-19 pandemic, has caused unprecedented changes to society as we know it. The effects have been particularly palpable in the practice of medicine. The medical community now has to re-evaluate everything we do on a daily basis, practices once deemed routine are now scrutinized. The field of otolaryngology has not been spared. We’ve had to significantly alter the way we provide care to patients, changes that are likely to become a new norm for the foreseeable future. This chapter will highlight some of the changes as they apply to otology/neurotology. Although this is written from the perspective of an academic physician, it is also applicable to private practice colleagues.